2011
DOI: 10.4202/app.2011.0090
|View full text |Cite
|
Sign up to set email alerts
|

New Early Jurassic gastropods from west-central Patagonia, Argentina

Abstract: A new gastropod fauna is reported from Chubut province of west−central Patagonia. Members of Trochoidea, Pseudomelanoidea, Campaniloidea, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…Previously known from Lomas Occidentales and Betancourt, Pliensbachian−Toarcian, Chubut Province, Argentina (Ferrari, 2013).…”
Section: Genus Procerithium Cossmann 1902mentioning
confidence: 99%
“…Previously known from Lomas Occidentales and Betancourt, Pliensbachian−Toarcian, Chubut Province, Argentina (Ferrari, 2013).…”
Section: Genus Procerithium Cossmann 1902mentioning
confidence: 99%
“…Bivalves, gastropods, cephalopods, brachiopods and corals were reported by these authors from several localities in the area, including Lomas Occidentales, Cerro La Trampa, Piedra Shotle and Lomas de Betancourt, which have yielded the most important Jurassic fossiliferous beds from the marine Mulanguiñeu Formation (Chubut Province). Another important marine locality was reported at the Early Jurassic of the Osta Arena Formation from the Pampa de Agnia region (central Chubut Province), known as Puesto Currumil (Ferrari, 2009(Ferrari, , 2012(Ferrari, , 2013Pagani et al, 2012). Preliminary biostratigraphic analyses carried out in the southern and west-central Chubut Province (Pagani et al, 2012;Ferrari, 2013Ferrari, , 2014a indicated a late Pliensbachian-early Toarcian age for these deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary biostratigraphic analyses carried out in the southern and west-central Chubut Province (Pagani et al, 2012;Ferrari, 2013Ferrari, , 2014a indicated a late Pliensbachian-early Toarcian age for these deposits. Moreover, Damborenea and Ferrari (2008), Ferrari (2009Ferrari ( , 2011aFerrari ( , b, 2012Ferrari ( , 2013Ferrari ( , 2014a, Ferrari et al (2014) and Pagani et al (2011Pagani et al ( , 2012 recently carried out new studies on the taxonomic composition of the faunas in the Early Jurassic of south-western and central Chubut Province, including the investigation of new fossil localities and the collection of Early Jurassic material.…”
Section: Introductionmentioning
confidence: 99%
“…Several Argentinean Early Jurassic marine gastropods have been described by Ferrari (2009Ferrari ( , 2011Ferrari ( , 2012Ferrari ( , 2013Ferrari ( , 2014aFerrari ( , 2014b and Ferrari et al (2014) from the Chubut Province. Up to date, 13 gastropod families from the Early Jurassic (late Pliensbachianearly Toarcian) marine deposits of the Mulanguiñeu and Osta Arena formations (Chubut Province), representing 20 genera, 2 subgenera and at least 30 species are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Damborenea et al (1975) preliminarily reported 15 gastropod species from the late Pliensbachian beds at Piedra Pintada (southern Neuquén), and Ferrari et al (in press) contributed to the paleontological knowledge of the family Trochotomidae in the Early Jurassic of the Neuquén basin. Recently, Ferrari (2011Ferrari ( , 2012Ferrari ( , 2013Ferrari ( , 2014aFerrari ( , 2014b Ferrari et al (2014) has described in detail and referred many gastropod species from Argentina to the genera Chartronella, Calliotropis, Ambercyclus, Colpomphalus, Cryptaenia, Guidonia, Hamusina, Jurassiphorus, Procerithium, Cryptaulax, Oonia, Striactaeonina, Actaeonina. Most of the species described thus far from Argentina show close taxonomic affinities to the Late Triassic gastropod faunas reported by Haas (1953) from the Pucará Group of Central Perú.…”
Section: Introductionmentioning
confidence: 99%